Mức độ sẵn sàng của sinh viên không chuyên ngữ trong bối cảnh tiếng Anh trở thành ngôn ngữ thứ hai: Nghiên cứu tại Trường Đại học Thủ đô Hà Nội - Hoa, Nguyễn Thị (Tạp chí Giáo dục, 2026)
In the context of globalization, the Vietnamese Government has approved the Project on Making English a Second Language in the National Education System for the period 2025-2035, with a vision to 2045. Assessing learner readiness, particularly among non-English-major students, is therefore essential for the effective and sustainable implementation of this policy. This study adopts a mixed-methods approach, combining qualitative and quantitative methods, to investigate the readiness of non-English-major university students to study in an educational environment where English is used as a second language. In addition, the study examines several factors influencing students’ readiness. Specifically, it focuses on students’ English language proficiency, their confidence in learning through English, their learning motivation, and their perceptions of the challenges they may encounter when using English as the medium of instruction in higher education. The findings are expected to indicate that although students generally hold positive attitudes toward the transition to English as the language of instruction, their levels of readiness vary considerably. The primary barriers to readiness include limited English proficiency and concerns about their ability to comprehend disciplinary knowledge when studying entirely in English. The findings provide empirical evidence to inform the development of an effective policy implementation roadmap and offer pedagogical implications, including strengthening language support services and adopting integrated content and language learning approaches.